A practical green chemistry approach to synthesize fused bicyclic 4H-pyranes via an amine catalysed 1, 4-addition and cyclization cascade. Issue 45 (19th April 2016) - Li, Jun-Long; Li, Qiang; Yang, Kai-Chuan; Li, Yi; Zhou, Liang; Han, Bo; Peng, Cheng; Gou, Xiao-Jun
Abstract : A new formal [4 + 2] cycloaddition in green solvent has been developed via amine catalysis, leading to efficient manufacture of novel bicyclic 4 H -pyranes incorporating γ-lactam functionalities. Abstract : A newly developed synthetic approach to densely functionalized 4 H -pyrane derivatives via an amine catalysed cascade reaction is presented. This protocol is relatively environmentally benign because it proceeds smoothly in water or ethanol at ambient temperature with low catalyst loading; more importantly, the products are easily purified, and some show promising antibacterial activity.